ФАУНА ЖУЖЕЛИЦ ГИССАРСКОГО ЗАПОВЕДНИКА - Халимов, Ф. З; Зокирова , Д.Ф (Actual problems and prospects of the study of the fauna, 2024)
For the first time, the species composition of ground beetles in the Gissar Reserve was studied. The carabidofauna of the reserve includes 82 species of ground beetles belonging to 9 subfamilies, 18 tribes and 36 genera. The taxonomic structure of the ground beetle fauna was studied. The most representative is the subfamily Harpalinae, which makes up 61% of the total species diversity (50 species).